Efficiency Of The Streamlined Post-Covid-19 Pandemic Curriculum: A Strategic Analysis Of Learning Depth And Educator Resilience - Anggi Fathoni Hidayat; Haji Awg Asbol bin Haji Mail (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The transition of the global education system in the post-COVID-19 era has prompted a paradigmatic shift from content-heavy curricula towards streamlined frameworks orientated around essential learning material. However, the efficiency of this streamlined model remains a subject of debate, caught between the demands for depth of competence and the adaptational burden placed upon educators in the field. This research seeks to re-examine the essence of efficiency in implementing streamlined curricula to optimise students' deep learning while simultaneously analysing its impact on teachers' workload and psychological well-being. Diverging from previous empirical designs, this study employs a qualitative methodology with a comprehensive Literature Review approach. The analysis synthesises various policy documents, international education reports, and reputable scientific literature published over the last decade (2016–2026). The desk research findings reveal the transformative dynamics of an essential curriculum in restoring the dignity of student learning and addressing learning loss without triggering educator burnout, provided it is supported by digital ecosystems and learning communities. The novelty of this research lies in the integration of adaptive technology variables and teacher agency as indicators of curricular efficiency dimensions frequently overlooked in conventional evaluative studies. These findings contribute to the formulation of an 'Agile Curriculum' model resilient to future disruptions. Practically, this study provides strategic recommendations for policymakers to harmonise teacher autonomy, administrative simplification, and the integrity of student understanding within the 'Kurikulum Merdeka' (Independent Curriculum) ecosystem, which has been fully implemented nationwide by 2026.